Units of Language Mixing: A Cross-Linguistic Perspective - Alexiadou, Artemis; Lohndal, Terje (Frontiers in Psychology, 2018)
Language mixing is a ubiquitous phenomenon characterizing bilingual speakers. A frequent context where two languages are mixed is the word-internal level, demonstrating how tightly integrated the two grammars are in the mind of a speaker and how they adapt to each other. This raises the question of what the minimal unit of language mixing is, and whether or not this unit differs depending on what the languages are. Some scholars have argued that an uncategorized root serves as a unit, others argue that the unit needs to have been categorized prior to mixing. We will discuss the question of what the relevant unit for language mixing is by studying word-internal mixing in Cypriot Greek-English, English-Norwegian, Greek-English, Greek-German, and Spanish-German varieties that have been reported in the literature based on data from judgment experiments and spoken corpora. By understanding and modeling the units of language mixing across languages, we will gain insight into how languages adapt to each other word-internally, and what some possible outcomes of language contact are in the minds of speakers.